2017
DOI: 10.1111/mice.12342
|View full text |Cite
|
Sign up to set email alerts
|

A Computer‐Aided Model for the Simulation of Railway Ballast by Random Sequential Adsorption Process

Abstract: This article presents a computer‐aided multistage methodology for the simulation of railway ballasts using the Random Sequential Adsorption (RSA – 2D domain) paradigm. The primary stage in this endeavor is the numerical generation of a synthetic sample by a “particle sizing and positioning” process followed by a “compaction” process. The synthetic samples of ballast are then visualized in the Computer‐Aided Design (CAD) environment. The outcomes of the simulation are analyzed by comparison with the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…The assessment of the geometry of the track-bed and its overall stability have been first a matter of research [10,19], whereas the focus has progressively moved towards the time-domain [14][15][16] and the frequency-domain [12,14,[20][21][22][23][24] analyses of the effects of fouling and fragmentation of ballast on the signal. In addition to this, new avenues in assessing quality of ballast aggregates have been recently explored by means of simulation-based approaches [25] and numerical models [26]. To the best of the authors' knowledge, although crucial pieces of information were derived from these studies, only few laboratory and test-site activities are actually reported in literature.…”
mentioning
confidence: 99%
“…The assessment of the geometry of the track-bed and its overall stability have been first a matter of research [10,19], whereas the focus has progressively moved towards the time-domain [14][15][16] and the frequency-domain [12,14,[20][21][22][23][24] analyses of the effects of fouling and fragmentation of ballast on the signal. In addition to this, new avenues in assessing quality of ballast aggregates have been recently explored by means of simulation-based approaches [25] and numerical models [26]. To the best of the authors' knowledge, although crucial pieces of information were derived from these studies, only few laboratory and test-site activities are actually reported in literature.…”
mentioning
confidence: 99%
“…The assessment of the geometry of the track-bed and its overall stability have been firstly investigated [10,19], whereas the focus has progressively shifted towards the time-domain [14][15][16] and frequencydomain [12,14,[20][21][22][23][24] analysis of the effects of fouling and fragmentation of the track-bed on the signal. In addition to this, new avenues in assessing quality of ballast aggregates have been recently explored by means of simulation-based [25] and numerical models [26].…”
Section: Ground-penetrating Radar For Ballast Assessmentmentioning
confidence: 99%
“…In this context, various sensors and non-destructive testing (NDT) techniques are available for the assessment and the health monitoring of bridges [5]. Amongst these, ground penetrating radar (GPR) [6][7][8], accelerometers [9], laser scanner [10][11], strain gauges [12], wireless network systems [13], ground-based interferometers [14], global position system (GPS) and levelling [15][16], are applied to transport infrastructures. Nevertheless, on-site sensors can be costly and cannot be installed on all the bridges at the network level, due to economic constraints.…”
Section: Introductionmentioning
confidence: 99%